Family Stabilit y and Mothers’ Perceptions of Elementary Learning Disabled Children: Implications for Counselling - Chapman, James W.; Whitford, Elaine M.; Boersma, Frederic J. (Canadian Journal of Counselling and Psychotherapy, 2012)
Sixty-two learning disabled (LD) and 69 normally achieving (NA) grade three children from 11 urban middle class elementary public schools were studied. The LD children were of average intellectual ability but receiving part-time remedial assistance for academic deficits, usually in the area of reading. Age, education, occupations,and income of parents, along with mother's current marital status and parental living arrangements were investigated. In addition, mother's perceptions of ability and achievement expectations with respect to their children's school performance were studied. The results showed that general demographic factors did not differentiate between the LD and NA children. However, significantly more LD than NA children came from homes which had experienced parental separation. It was also found that LD mothers had significantly lower perceptions of their children's academic abilities and lower expectations for future success than NA mothers. The findings are discussed in terms of the relationship between family stability and learning disabilities, along with the need for parent counselling to facilitate mor epositive perceptions and expectations, and improved achievement in school for LD children.